2022
DOI: 10.15282/ijame.19.2.2022.12.0754
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Exergy Analysis of a Shell and Tube Heat Exchanger using PGW based ZnO Nanofluids

Abstract: In this experimental work, ZnO nanoparticles were synthesized using the chemical precipitation method, and the nanoparticle structure and morphology were characterized through XRD and SEM. Heat transfer and exergetic characteristics were then studied in a shell and tube heat exchanger using PGW-based ZnO nanofluids varying nanoparticle volume concentration and nanofluid (shell side) flow rate at 6, 8, 10 and 12 litres/min. The hot water flow rate was fixed at 12 litres/min. The experimental results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…For instance, a study conducted by Liu et al [ 11 ] showed that the use of nanofluids enhanced the efficiency of the solar collector by 25%. Another example, using ZnO nano-fluid, the heat transfer coefficient of a shell and tube heat exchanger is enhanced by 40% [ 12 ]. The performance of nanofluids in various energy applications has been extensively reviewed in the literature, with a primary focus on assessing the sustainability of different types of nanofluids [ [13] , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study conducted by Liu et al [ 11 ] showed that the use of nanofluids enhanced the efficiency of the solar collector by 25%. Another example, using ZnO nano-fluid, the heat transfer coefficient of a shell and tube heat exchanger is enhanced by 40% [ 12 ]. The performance of nanofluids in various energy applications has been extensively reviewed in the literature, with a primary focus on assessing the sustainability of different types of nanofluids [ [13] , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%